2014
DOI: 10.1017/s0022215114003119
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal airway stenting devices for obstructive sleep apnoea: A systematic review and meta-analysis

Abstract: Objective: To systematically review outcomes of adults with obstructive sleep apnoea treated with nasopharyngeal airway stenting devices.Methods: Medline, Scopus, Web of Science and the Cochrane Library databases were searched, and data on device use and tolerability, sleepiness, oxygen saturation, apnoea index, apnoea-hypopnoea index, and sleep quality were collected.Results: Of 573 potential studies, 29 were retrieved for detailed evaluation and 16 met the study criteria. Polysomnography data for patients tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 32 publications
1
43
0
1
Order By: Relevance
“…Although we did not classified our patients in accordance to the Fujita classification, all subjects who showed ameliorated OSA and snoring by using the s-NAS would be classified in Fujita type I [22]. As we expected, on the basis of features of the s-NAS (length, structure, and design), the device was not effective in one subject with mild OSA and tonsillar hypertrophy and it was unable to normalize the AHI in severe OSA; these findings were consistent with those in previous studies of nasal and oral appliances [12,14,17,18]. Intriguingly, the device improved the number of apnea events, rather than the number of hypopnea events, in subjects with varying degrees of severity of OSA (Figure 2).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Although we did not classified our patients in accordance to the Fujita classification, all subjects who showed ameliorated OSA and snoring by using the s-NAS would be classified in Fujita type I [22]. As we expected, on the basis of features of the s-NAS (length, structure, and design), the device was not effective in one subject with mild OSA and tonsillar hypertrophy and it was unable to normalize the AHI in severe OSA; these findings were consistent with those in previous studies of nasal and oral appliances [12,14,17,18]. Intriguingly, the device improved the number of apnea events, rather than the number of hypopnea events, in subjects with varying degrees of severity of OSA (Figure 2).…”
Section: Discussionsupporting
confidence: 87%
“…Some previous studies have reported oral or nasopharyngeal appliances as non-surgical alternatives to CPAP for OSA patients who do not tolerate CPAP treatment [12][13][14][15][16][17][18]. Although the concept of nasopharyngeal tube insertion to maintain airflow through the upper airway during sleep was proposed in the 1980s and has been reviewed before [7,12,18], such devices are not currently in common use. The nasal trumpet has been used successfully to decrease airway obstruction in the short term, such as immediately after surgery for OSA [18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kumar and colleagues review the evidence for the use of nasopharyngeal airway stenting devices in OSA patients. 5 In this respect, the evidence is mixed: some stenting devices have shown limited effectiveness and low tolerability, whereas others have shown significant benefit with high patient acceptability. Another article, by Acar and colleagues, investigates the effect of OSA on oral and dental health, 6 with the knowledge that open-mouth breathing can have an adverse effect.…”
mentioning
confidence: 99%